Arenas of fragile alliance making. Space and interaction in precarious migrant protest in Berlin and Vienna. (4th March 2022) - Ataç, Ilker; Steinhilper, Elias
ABSTRACT: Comparing migrant protests in Berlin and Vienna, this article analyses dynamics of alliance making in precarious mobilizations. It suggests that a 'players and arenas' perspective allows shedding light on the contentious and fragile interactions among a heterogeneous set of players typical for protests in contexts of marginalization. These interactive dynamics involve migrants with various legal status and social backgrounds as well as supporting grassroots activists and NGOs. The article furthermore illustrates how the specific characteristics and locations of protest arenas, as camps or as occupied buildings influence alliance (un)making and hence, contribute to protest incubation and fragmentation.